KEMAMPUAN INTERPERSONAL SKILLS MAHASISWA PROGRAM STUDI PENDIDIKAN TATA NIAGA FAKULTAS EKONOMI UNIVERSITAS NEGERI SURABAYA - ARIFIN, MUHAMMAD (Jurnal Pendidikan Tata Niaga (JPTN), 2013)
At this time not much research about the soft skills of interpersonal skills especially in education, but in particular the role of the soft skills of interpersonal skills is essential. This is evidenced by studies that reveal the role stout soft skills more influential role in one's success than hard skills inherent in a person. Interpersonal skills study aims to determine the results of the depiction of interpersonal skills in students of business administration education economics faculty at the Universitas Negeri Surabaya. This research was carried out by using observation and interviews to students of business administration education class of 2009 totaled 48 students. The results showed that the ability of interpersonal skills of students class showed satisfactory results, this is evidenced by the majority of students have a lot of the interpersonal skills contained in the study variant on each sub-focus of research. Keywords: Interpersonal skills, student, business administration.